Efectividad del tratamiento con atorvastatina en pacientes con hígado graso no alcohólico - Castro Carranza, Katia Paola (2020)
Non-alcoholic fatty liver disease (NAFLD: Non-Alcoholic Fatty Liver Disease) is a major public health problem worldwide, considered as a reflection of a systemic disease and also as the hepatic component of metabolic syndrome. An effective drug therapy for this entity is not yet available. Statins are a group of drugs that inhibit HMG-CoA-reductase with pleiotropic effects proven decades ago, being atorvastatin a drug that has been used experimentally in patients with NAFLD, proving its beneficial effect, as it reduces fibrosis and cardiovascular complications , decreases transaminase levels, reduces the risk of hepatocellular carcinoma and also works as an anti-inflammatory in this type of patients. Its dosing in low to moderate doses (20-40 mg daily) in NAFLD appears to be safe and atorvastatin is postulated to have a predominantly hepatoprotective rather than hepatotoxic safety profile. Problem: Is atorvastatin an effective drug in the treatment of nonalcoholic fatty liver? Objective: To demonstrate the efficacy of atorvastatin in the treatment of non-alcoholic fatty liver.